Antibodies against hepatitis C virus in hemodialysis patients - Refik MAS; Selim NALBANT; Yavuz SAYKAL; Ümit ATEŞKAN; Ayhan DİNÇ and Tahir ÜNAL and Fikri KOCABALKAN (Turkish Journal of Gastroenterology, 2019)
-